Effectiveness and implementation of a primary healthcare intervention for multimorbidity and frailty among urban older adults in India: Protocol for the Multi-FrAME cluster randomized trial - Jaya Singh Kshatri; Haimanti Bhattacharya; Siddhartha Goutam; Ashok Kumar Mahakuda; Rasmiranjan Nayak; Kavitha Adukkadukam Kambikanam; Tanveer Rehman; Abhinav Sinha; Mamata Manjari Sahu; Kshanaprava Mohakud; Purna Chandra Das; Sanghamitra Pati (PLoS ONE, 2026)
The worldwide impact of multimorbidity and frailty is accelerating among older adults, particularly in India, where healthcare systems face resource constraints. Multimorbidity defined as the coexistence of two or more chronic health conditions, and frailty—a state of heightened vulnerability—jointly result in functional disability, decreased quality of life, and increased healthcare use. Despite this, primary healthcare frameworks in India lack integrated geriatric care models. The study addresses this gap by evaluating a culturally appropriate, multicomponent intervention to improve quality of life related to health status and wellbeing among older adults in urban Odisha. The Multimorbidity-Frailty among elderly (Multi-FrAME) study is a phase 3, two-arm, cluster-randomized, observer-blinded trial that will be conducted across 10 urban Primary Healthcare Centres (UPHCs) in Bhubaneswar, Odisha. Eligible participants will be enrolled and randomized at the cluster level. The intervention group will receive a structured, monthly multicomponent package delivered through UPHCs whereas the control group will be given standard care. The primary outcome will include change in EuroQol 5-Dimension 5-Level (EQ-5D-5L) quality of life score at 6 and 12 months, and secondary outcomes will be a change in frailty, function, healthcare use, medication adherence and mortality. Data will be collected by trained, blinded assessors using validated tools and analyzed using mixed-effects regression models. Institutional ethical clearance was obtained for the study. The Multi-FrAME trial addresses a critical gap in geriatric care by evaluating a scalable, multicomponent intervention for frailty and multimorbidity within India’s primary healthcare system. Leveraging existing infrastructure and non-specialist staff, it integrates medical, nutritional, physical, and psychosocial support. Findings will inform policy and offer a replicable model for integrated elder care in Low and Middle Income Countries (LMICs). Trial Registration was done in Clinical Trial Registry of India (linked to WHO registry of trials) with registration no CTRI/2024/09/073487 on 5 th September,2024.